Study on capacity of improved lithium iron phosphate battery for grid energy storage - Yan Bofeng; Zeng Ming (Functional Materials, 2019)
This article discusses the structure and use of cathode materials with iron phosphate ions. Improved iron phosphate nanoplates were obtained, their electrochemical properties were analyzed, especially in the case of direct current, their charge and discharge times were studied. The energy accumulator based on LiFePO₄ was studied, the reliability of the results is confirmed by situational studies.